Pengaruh Motivasi Terhadap Kinerja Masinis UPT KRU KA Lubuk Linggau - Tutik Pebrianti; Imam Suroso; Nanda Revita; Vivin Avini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study entitled the effect of work motivation on the performance of train drivers UPT Lubuk Linggau train crew. This study aims to determine the effect work motivation on the performance of train drivers UPT Lubuk Linggau train crew. The population in this study were all machinists in the Lubuk Linggau train crew which were sampled as many as 22 respondents. Sampling is done by saturated or census samples. The technique used is a simple linear regression. The results showed that work motivation had a positive and significant effect on the performance of train drivers Lubuk Linggau train crew with the value of the t test results obtained the t value of the work motivation variable was 7.452 greater than the t table value of 1.721 and significant t of 0,000 < α (0,05). The work motivation variable regression coefficient of 0.412 indicates that any change or increase in work motivation variable of 1 will result in an increase or affect the train driver’s performance by 41.2%. work motivation variables can be explained or affect the performance variable of drivers UPT Lubuk Linggau train crew while the rest is equal 26.5% are influenced by other factors not discussed in this study such as discipline, commitment, organizational culture and other factors.